2021
DOI: 10.3389/fnhum.2021.706550
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Insight Questions Inventory and Visual Support Strategies on Carer-Reported Quality of Life for Children With Cerebral Palsy and Perceptual Visual Dysfunction in Nigeria: A Randomized Controlled Trial

Abstract: Structured clinical history question inventories have previously been used to try and elicit symptoms of perceptual visual dysfunction (PVD) in children with cerebral palsy (CP) in different settings. Earlier studies have suggested that PVD may affect quality of life and specific habilitational strategies, linked to inventory responses, may improve quality of life. Through an RCT, based on a community based sample of children with CP in Cross River State, Nigeria, we aimed to determine if a structured history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Seven interventions studies were identified, which used strategies to increase visual function and maximize current functional abilities through adaptations to daily tasks and modifications to the environment. One RCT examined if giving caregivers visual support strategies from the Insight Question Inventory improved the quality of life of children with CP in the intervention group compared to those in the control group who did not receive these strategies 27 . The intervention group was asked to use the strategies at least three times per day for 6 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven interventions studies were identified, which used strategies to increase visual function and maximize current functional abilities through adaptations to daily tasks and modifications to the environment. One RCT examined if giving caregivers visual support strategies from the Insight Question Inventory improved the quality of life of children with CP in the intervention group compared to those in the control group who did not receive these strategies 27 . The intervention group was asked to use the strategies at least three times per day for 6 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…One RCT examined if giving caregivers visual support strategies from the Insight Question Inventory improved the quality of life of children with CP in the intervention group compared to those in the control group who did not receive these strategies. 27 The intervention group was asked to use the strategies at least three times per day for 6 weeks. Overall, there was no change in quality of life on the PedsQL 4.0 Generic or PedsQL 3.0 for CP.…”
Section: Task Adaptations and Environmental Modificationsmentioning
confidence: 99%
“…According to various research, the prevalence of visual impairment in CP children ranges from 40 to 50% of kids. In CP, visual impairment is frequently caused by the same brain injury that results in movement issues (18) . Up to 39% of CP patients experience hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Some attempts to bridge this gap exist (e.g., CVIT 3–6, Vancleef et al, 2020 ). Adoption of existing tools will likely require modifications for culture (Duke et al, 2021 ) and low-level abilities to be appropriate for impacted children.…”
Section: Discussionmentioning
confidence: 99%